Association of C-reactive protein and D-dimer with diffusing lung capacity for carbon monoxide as a pulmonary post-COVID-19 sequelae: A systematic review - Tan, Heidi Kristine C. (Animo Repository, 2023)
C-reactive protein (CRP) and D-dimer are biomarkers that are well-established prognostic factors for COVID-19 severity and mortality. However, there is limited knowledge on the association of these biomarkers with post-COVID-19 sequelae. On the other hand, impairment of lung diffusing capacity for carbon monoxide (DLCO) is one of the frequently recorded pulmonary abnormalities among recovering COVID-19 patients, but there is no clear understanding regarding the possible relationship between DLCO and post-COVID-19 sequelae. Considering these factors, this systematic review aimed to determine the relationship between CRP and D-dimer levels and pulmonary post-COVID-19 sequelae based on DLCO. The investigation involved a search for articles published within three (3) databases from March 2020 until February 2023. From the thirty (30) studies included, four types of relationships between biomarkers and DLCO were identified, namely the combinations of elevated biomarker and normal DLCO, elevated biomarker and low DLCO, normal biomarker and low DLCO, and normal biomarker and normal DLCO. Moreover, the most common relationship was observed to be the combination of normal biomarker level and reduced predicted DLCO. However, definitive conclusions could not be drawn due to the variability in the point of comparison used. Further evaluation was conducted to obtain more insights into the relationships, but there were no consistent associations found despite examination of similar compared groups. Given the varying relationships of CRP and D-dimer level and DLCO, along with the discrepancies determined in the analysis by point of comparison, it can be concluded that there is no association between biomarker levels and lung diffusing capacity in recovering COVID-19 patients. Further research should aim to utilize studies with similar study designs, as well as a uniform point of comparison and follow-up duration, to fully understand this relationship and its implications for post-COVID-19 sequelae. Moreover, in the Philippine context, there is a need for more studies that will analyze post-COVID-19 data from hospitals across the country to better understand the current situation and improve long-term treatment and management strategies.